Sulfonated Mesoporous Silica-Carbon Composite Derived from a Silicate-Polyethylene Glycol Gel and Its Application as Solid Acid Catalysts - Shofiyya Julaika; Agus Farid Fadli; Widiyastuti Widiyastuti; Heru Setyawan (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Solid acid catalyst is a promising alternative to the counterpart homogeneous acid for esterification reaction from the viewpoint of reusability and environmental concerns. This work aims to develop sulfonated mesoporous silica-carbon composite as solid acid catalyst for the esterification. The catalyst was synthesized from sodium silicate as the silica precursor and polyethylene glycol (PEG) as both carbon precursor and template via a sol-gel route in an aqueous system. Then, it was carbonized to produce mesoporous silica-carbon composite. Using the proposed method, the surface area of the silica-carbon composite could reach as high as 1074.21 m2/g. Although the surface area decreased to 614.02 m²/g when it was functionalized with sulfonate groups, the composite had a high ionic capacity of 5.3 mEq/g and exhibited high catalytic activity for esterification reaction of acetic acid with ethanol. At a reaction temperature of 80 °C, the acetic acid conversion reached 76.55% in 4 h. In addition, the catalyst had good reusability, which can be comparable with the commercial catalyst Foltrol F-007. It appears that the sulfonated silica-carbon composite prepared from sodium silicate using PEG as the carbon source a promising candidate as catalyst for esterification and the related area. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).